Bed rails in an internal medicine clinical setting: a medico-legal analysis based on a systemic review of available literature - Tozzo, Pamela; Cestonaro, Clara; Menozzi, Lorenzo; Caenazzo, Luciana (Medicina e Morale, 2021)
The use of restraints and, specifically, bed rails embody a controversial topic. Bedrails are commonly considered to be a protective device; however, they may be used as a form of restraint, and they may lead to severe injuries. Often restraints are used despite the lack of indication and prescription, without complete informed consent and without adequate reporting in medical records. Due to these reasons, restraints may lead to lawsuits. We present two cases where the use of physical restraints was complicated by health consequences, leading to litigation and medico-legal evaluation of medical and/or nurse liability.